Part A can be solved using the following formula:
Δt = Δtp * squareroot( 1 - (v/c)^2) (*where Δt is observed time, Δtp is proper time)
Δtp can be calculated as follows:
v = d/t (*where v=velecity, d=distance, t=time)
therefore solving for t:
Δtp = d/v
After calculating Δtp, plug back into the first formula and solve for Δt.
Part B is solved with the following formula:
L = Lp * squareroot( 1 - (v/c)^2) (*where L=observed length, Lp=proper length)
Lp is simply the given distance, plug in the values into the formula and that is your answer.